Compassion Fatigue and Coping Strategies among Nurses in a Tertiary Hospital in North-Central Nigeria: A Facility-Based Cross-Sectional Study - Emmanuel Anyebe (The Nursing Scope, 2026)
Background: Compassion fatigue (CF) may develop following nurses’ repeated exposure to the suffering and traumatic experiences of patients in their care, potentially affecting their psychological well-being and professional functioning. Aim: This study assessed the prevalence of compassion fatigue, its contributing factors, and coping strategies among nurses in a tertiary hospital in North-Central Nigeria. Method: A facility-based cross-sectional study was conducted among 170 nurses across various clinical departments. Data were collected using a structured questionnaire incorporating items from the Professional Quality of Life Scale (ProQOL 5) and the Brief-COPE inventory. Data were analysed using descriptive and inferential statistics with IBM SPSS Statistics version 22. Chi-square tests were used to examine associations between selected variables and compassion fatigue. Findings: Most nurses (81.2%) had moderate compassion fatigue, 11.8% had high compassion fatigue, and 7.1% had low compassion fatigue. Moderate burnout was reported among 95.9% of participants, while 79.4% experienced moderate secondary traumatic stress. Reported contributing factors, based on combined Agree/Strongly Agree endorsement, included insufficient rest (73.5%), emotionally demanding work environments (69.4%), and heavy workload (68.2%). Compassion satisfaction was moderate among 68.8% of nurses and high among a further 29.4%. Participants employed both problem-focused and emotion-focused coping strategies, with acceptance, action planning, positive reframing, and spiritual coping among the commonly reported approaches. A statistically significant association was found between years of clinical experience and compassion fatigue (χ² = 56.315, df = 6, p < .001). However, the association between clinical unit and compassion fatigue was not statistically significant (Fisher–Freeman–Halton exact p = .278; χ² = 7.962, df = 6, for reference). Conclusion: Compassion fatigue was predominantly moderate among nurses in the study setting and coexisted with substantial levels of burnout and secondary traumatic stress. Nurses employed diverse coping strategies to manage the emotional demands associated with clinical practice. Recommendation: Hospital management should strengthen institutional support through accessible mental health services, resilience-building programmes, adequate rest periods, and equitable shift scheduling. Nursing professional associations and regulatory bodies should also develop guidelines that promote nurses’ psychological well-being and effective coping with occupational stress. Keywords: Burnout, Compassion Fatigue, Coping Strategies, Nurses, Secondary Traumatic Stress, Nigeria.